Tools for Productively Managing Conflict. (1st June 2012) - Zucker, Deborah
Abstract : In scientific teams as in life, conflicts arise. This paper aims to provide an introduction to tools and skills to help in managing conflicts in practice. Using a structured approach enables the concerns and interests of all involved to be identified and clarified. It also permits a better understanding of yourself and others and will help empower those in conflict to find acceptable and workable resolutions.